No limiar da escrita argumentativa: um estudo exploratório - Costa, Ana Luísa (2018)
The aim of this paper is to contribute with some empirical evidence to the study of the development of argumentative writing. Curricular documents and Portuguese syllabi over the past 30 years have neglected argumentative writing, as the writing of personal opinion texts in the 1st cycle of Basic Education. Although some literature on writing development conceives argumentative writing as a late skill, some research on argumentative writing development brings into debate the importance of promoting writing skills within different textual genres, specifically with argumentative texts, in order to improve linguistic literacy and increase writing skills.